2006
DOI: 10.1143/jjap.45.8046
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inductively-Coupled RF Plasma Sources with Multiple Low-Inductance Antenna Units

Abstract: We have developed a cylindrical RF plasma source by the inductive coupling of multiple low-inductance antenna (LIA) units and analyzed the plasma density profile of this source using fluid simulation. Experiments using four LIA units showed a stable source operation even at 2000 W RF power, attaining plasma densities as high as 1011–1012 cm-3 in an argon pressure range of 0.67–2.6 Pa. The amplitude of antenna RF voltage was measured to be less than 600 V, which is considerably smaller than those obtained using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…The profile of temporarily averaged floating potential was comparatively decreased gradually away from the antenna, as shown in Figure 2(c), and the values were significantly small. The low floating potential is primarily considered to be partially due to the reduction in antenna RF voltage obtained by decreasing antenna inductance 9,10. The floating potential at the powered and grounded sides of the antenna was found to decrease considerably while approaching the chamber wall, whereas the fluctuation of the floating potential at the powered and grounded sides of the antenna was found to increase considerably while approaching the wall as shown in Figure 3(a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The profile of temporarily averaged floating potential was comparatively decreased gradually away from the antenna, as shown in Figure 2(c), and the values were significantly small. The low floating potential is primarily considered to be partially due to the reduction in antenna RF voltage obtained by decreasing antenna inductance 9,10. The floating potential at the powered and grounded sides of the antenna was found to decrease considerably while approaching the chamber wall, whereas the fluctuation of the floating potential at the powered and grounded sides of the antenna was found to increase considerably while approaching the wall as shown in Figure 3(a).…”
Section: Resultsmentioning
confidence: 97%
“…To solve these problems, we have developed ICP sources with multiple low‐inductance antenna (LIA) units, which are fully covered with dielectric tubing for complete isolation from the plasma. In our previous studies, we have demonstrated that this unique antenna for ICP generation allows high‐density (10 11 –10 12 cm −3 ) plasma production with low plasma damage (as low as 10 V) via low‐voltage operation of ICPs and internal‐antenna configuration with LIA units has the feature of flexibility to meet various configuration of plasma sources 9,10…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [10][11][12][13][14][15][16], we demonstrated that the configuration with multiple LIA units for ICP generation allowed high-density (10 11 -10 12 cm − 3 ) plasma production with high power-transfer efficiency (as high as 90%) and low plasma potential (as low as 6 V). The ICP sources with LIA units are considered to be one of the most promising candidates as plasma sources for low-damage and high-quality processes [17,18].…”
Section: Introductionmentioning
confidence: 97%
“…In our previous studies [10][11][12][13][14][15][16], we have demonstrated that this unique antenna for ICP generation allows high-density (10 11 -10 12 cm − 3 ) plasma production with low plasma damage (as low as 10 V) via low-voltage operation of ICPs. Furthermore the internal-antenna configuration with the LIA units has the feature of flexibility to meet various configurations of plasma sources.…”
Section: Introductionmentioning
confidence: 99%